Penyuluhan perilaku hidup bersih dan sehat (oral hygiene) di Sekolah Pendidikan Anak Usia Dini Ayah Bunda Sayang, Lombok Barat - Nurmi Hasbi; Rosyunita; Adelia Riezka Rahim (INDRA: Jurnal Pengabdian kepada Masyarakat, 2023)
The mouth and teeth are one of the entry points for microorganisms such as fungi, bacteria and so on which can cause health problems. Oral and dental health can be achieved by implementing clean and healthy living behaviors (PHBS) oral hygiene such as brushing your teeth properly and being able to keep your toothbrush clean. This community service activity aims to increase the knowledge of young children regarding the practice of maintaining oral and dental health. The method of activity that the author uses is in the form of counseling and mentoring with lecture methods, discussions, and demonstrations on how to brush your teeth properly and correctly. This activity was attended by 16 participants. The player is accompanied by the teacher to fill out the questionnaire. The results of the questionnaire showed that almost of the PKM participants had not properly implemented the behavior of maintaining oral and dental hygiene. Participants took part in this counseling enthusiastically and the results of the evaluation revealed that all participants understood oral hygiene behavior, namely knowing the practice of brushing their teeth and how to maintain cleanliness in brushing their teeth